Macrophage Depletion in Elderly Mice Improves Response to Tumor Immunotherapy, Increases Anti-tumor T Cell Activity and Reduces Treatment-Induced Cachexia - Duong, Lelinh; Radley-Crabb, Hannah G.; Gardner, Joanne K.; Tomay, Federica; Dye, Danielle E.; Grounds, Miranda D.; Pixley, Fiona J.; Nelson, Delia J.; Jackaman, Connie (Frontiers in Genetics, 2018)
Most cancers emerge in the elderly, including lung cancer and mesothelioma, yet the elderly remain an underrepresented population in pre-clinical cancer studies and clinical trials. The immune system plays a critical role in the effectiveness of many anti-cancer therapies in young hosts via tumor-specific T cells. However, immunosuppressive macrophages can constitute up to 50% of the tumor burden and impair anti-tumor T cell activity. Altered macrophage phenotype and function during aging may further impact anti-tumor T cell responses. Yet, the impact of macrophages on anti-tumor T cell responses and immunotherapy in the elderly is unknown. Therefore, we examined macrophages and their interaction with T cells in young (3 months) and elderly (20-24 months) AE17 mesothelioma-bearing female C57BL/6J mice during tumor growth. Mesothelioma tumors grew faster in elderly compared with young mice, and this corresponded with an increase in tumor-associated macrophages. During healthy aging, macrophages increase in bone marrow and spleens suggesting that these sites have an increased potential to supply cancer-promoting macrophages. Interestingly, in tumor-bearing mice, bone marrow macrophages increased proliferation whilst splenic macrophages had reduced proliferation in elderly compared with young mice, and macrophage depletion using the F4/80 antibody slowed tumor growth in young and elderly mice. We also examined responses to treatment with intra-tumoral IL-2/anti-CD40 antibody immunotherapy and found it was less effective in elderly (38% tumor regression) compared to young mice (90% regression). Tumor-bearing elderly mice decreased in vivo anti-tumor cytotoxic T cell activity in tumor draining lymph nodes and spleens. Depletion of macrophages using F4/80 antibody in elderly, but not young mice, improved IL-2/anti-CD40 immunotherapy up to 78% tumor regression. Macrophage depletion also increased in vivo anti-tumor T cell activity in elderly, but not young mice. All the tumor-bearing elderly (but not young) mice had decreased body weight (i.e. exhibited cachexia), which was greatly exacerbated by immunotherapy; whereas macrophage depletion prevented this immunotherapy-induced cachexia. These studies strongly indicate that age-related changes in macrophages play a key role in driving cancer cachexia in the elderly, particularly during immunotherapy, and sabotage elderly anti-tumor immune responses.